Assessment of the sedimentation and trapping efficiency in dam reservoirs by applying the settling basin framework - Bérenger Koffi; Koffi Eugène Kouakou; Alexis Loukou Brou; Martin Sanchez; Ouédé Gla Blaise; Brice Wawogninlin Coulibaly; Franck Hervé Akaffou; Michal Habel; Amani Michel Kouassi; Dibi Brou; Kouakou Lazare Kouassi (Journal of Hydrology: Regional Studies)
Study region: The investigated object is the Lobo Dam reservoir, located in the south part of the Lobo River Basin in west-central Côte d’Ivoire, West Africa. Study focus: Dam reservoirs in tropical climates face rapid siltation and eutrophication challenges, necessitating new analytical solutions to understand their capacity to trap sediment inputs. This study presents a hydrosedimentary mathematical model based on the theory of settling basins and Gamma Law approaches to describe the settling velocity of suspended solids. Using field data from the Lobo River reservoir in Côte d′Ivoire. New hydrological insights for the region: The analysis shows that the reservoir's trapping capacity is influenced by settling velocity, critical velocity, shape parameter 1/r, and the Peclet number (Pe). The study found strong synchronization between models for constant settling velocity (CV-NT, CV-CM, CV-Teeter (1986)) and variable settling velocity (VV-NT, VV-CM) with Teeter’s (1986) model. This agreement validates the proposed models. However, for Pe > 4, the numerical values and curves fall outside the validity range of Teeter’s (1986) model, particularly during dry periods.The findings provide crucial insights into the hydrosedimentary dynamics of the Lobo River reservoir, emphasizing the need to account for seasonal variations and hydrological conditions. This research offers valuable guidance for sediment and water resource management, contributing to the sustainability of reservoirs in tropical regions facing similar environmental pressures.